Chemical diversity and incubation time affect non-additive responses of soil carbon and nitrogen cycling to litter mixtures from an alpine steppe soil. (June 2017) - Chen, Youchao; Ma, Shuqin; Sun, Jian; Wang, Xiaodan; Cheng, Genwei; Lu, Xuyang
Abstract: The mechanisms of litter-mixing effects on soil carbon (C) and nitrogen (N) cycling in alpine ecosystems remain inconclusive. In this study, we employed a four-month litter-mixing experiment to examine the relationship between litter chemical diversity, incubation time and litter-mixing effects on soil C and N fluxes from an alpine steppe ecosystem in Northern Tibet. Litter mixtures caused predominantly non-additive effects on soil C and N fluxes, with more synergistic effects for carbon dioxide (CO2 )/nitrous oxide (N2 O) emissions while more antagonistic effects for soluble organic C (SOC), total inorganic N (TIN), microbial biomass C (MBC) and urease activity (UA). Litter-mixture would largely increase the fluxes of CO2, N2 O emission and SON, while decrease SOC, TIN, MBC and UA concentration. We calculated six chemical diversity indices, and found litter chemical diversity correlated with the strength of litter-mixing effect on soil C and N, but the indices we chose may be influenced our understanding of the relationship. Our results also showed that models including the chemical diversity indices and incubation time generally gave better explanation on variations of litter-mixing effects. This work demonstrated a general relationship between litter chemical diversity and non-additive responses of soil C and N cycling, and suggested that incubation time is an important factor in understanding the litter-mixing effects. Highlights: Dynamics of soil C and N fluxes under mixed-litter decomposition is presented. Non-additive effects of mixed litters on soil C and N fluxes are predominant. Non-additive effects of mixed litters on soil C and N fluxes are not systematic. Litter chemical diversity and incubation time affect non-additive effects. Multiple chemical diversity indices are recommended in litter-mixing effects study.